Hypertension burden and challenges across the hypertension treatment cascade among adults enrolled in HIV care in northern Tanzania. Issue 8 (11th July 2020) - Manavalan, Preeti; Madut, Deng B.; Hertz, Julian T.; Thielman, Nathan M.; Okeke, Nwora Lance; Mmbaga, Blandina T.; Watt, Melissa H.
Abstract: Failure to address hypertension among people living with HIV (PLWH) may undermine the significant progress made toward reducing mortality among this high‐risk population in sub‐Saharan Africa (SSA). Here, the authors report hypertension prevalence, diagnosis, and treatment among patients enrolled in HIV care in Tanzania. Patients attending an HIV clinic were consecutively screened for hypertension. Hypertension was defined as follows: a single blood pressure measurement ≥160 mm Hg systolic or ≥100 mm Hg diastolic, two measurements at separate visits ≥140 mm Hg systolic or ≥90 mm Hg diastolic, or self‐reported hypertension diagnosis. The authors screened 555 patients, and 19.6% met hypertension criteria. Among a subset of 91 hypertensive participants, 44 (48.4%) reported previous blood pressure measurements, 32 (35.2%) were aware of diagnosis, 10 (11.0%) reported current antihypertensive use, and none had controlled blood pressure. Addressing barriers along the hypertension treatment cascade must be a top priority to improve cardiovascular outcomes among PLWH in SSA.